English Bestselling Fiction Study in the Context of Twentieth and Early Twenty-first Centuries - Ta Thi Thanh Huyen, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
Bestselling fiction is an interesting and controversial phenomenon which attracts the attention of a wide range of academic circles from many areas such as socio-economic study, cultural study and literary study in nearly one hundred years. It has been studied firstly in English speaking countries where it was born, then extended to many other countries in Europe, America, Asia, and Pacific Islands. In Viet Nam, due to the newly formed market economy in postwar period, this phenomenon has just sprouted in Doi Moi literature. According to our investigation, there has not any theoretical and systematical research on this object in Viet Nam except for some short papers, not to mention applied studies. It is a gap need filling as soon as possible. The result of the first step of this task is introduced concisely in this paper that is a summarization of English bestselling fiction studies in the context of twentieth and early twenty-first centuries.Received 7th August 2023; Revised 15th September 2023; Accepted 30th September 2023